2009
DOI: 10.1227/01.neu.0000356984.92242.d5
|View full text |Cite
|
Sign up to set email alerts
|

Do Intracranial Neoplasms Differ in Ollier Disease and Maffucci Syndrome? An in-Depth Analysis of the Literature

Abstract: OD and Maffucci syndrome differ with respect to the distribution of intracranial malignancies by histology, and geographical and age distribution of cases, with OD patients younger by approximately a decade, and Maffucci syndrome patients more likely to live in Asia or South America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 74 publications
1
36
0
2
Order By: Relevance
“…Chromosomal imbalances in this region are detected in highly malignant human colon cancer cell lines [Ranger and Szymczak, 2009]. The third locus, 14q11.2, is associated with lymphoma, meningioma and adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal imbalances in this region are detected in highly malignant human colon cancer cell lines [Ranger and Szymczak, 2009]. The third locus, 14q11.2, is associated with lymphoma, meningioma and adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Initial genetic studies demonstrated a normal karyotype and subsequent theories concerning mutations of the parathyroid hormone receptor PTH1R have been suggested and disproved [6][7][8]. One case of Maffucci's syndrome has been reported with an inversion of chromosome bands p11 and p21 of chromosome 1, however no other cases have been identified [2].…”
Section: Discussionmentioning
confidence: 99%
“…Bei beiden Erkrankungen sind außer-dem Angiosarkome, Hirntumoren und hepatobiliäre Neoplasien beschrieben worden, die häufig für die Lebenserwartung der Patienten bedeutsamer sind (Literatur bei [28]). Die Erkrankung ist auf Mutationen im EXT1-und EXT2-Gen zurückzuführen, die auf Chromosom 8q24.1 und Chromosom 11p11-p12 lokalisiert sind.…”
Section: Enchondromatoseunclassified